The role of the external auditor in reviewing internal control in electronic accounting systems: Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2023)
This study aimed to identify the role of the external auditor in reviewing internal control in electronic accounting systems. To achieve the objective of the study, the descriptive analytical approach was followed. The study sample consisted of (62) external auditors in the Kingdom of Saudi Arabia. The result shows that there is a high and strong level of agreement among the sample members about the role of the external auditor in the internal control review. The agreement of the participants on the importance of electronic accounting systems in the internal audit is high. The study also concluded that there is a statistically significant impact on the role of the external auditor in reviewing internal control in electronic accounting systems and that the external auditor has a great role and importance that contributes to the review of internal control in electronic accounting systems, with a rate of 59.9%. Also, there is a statistically significant impact on the role of the external auditor (reliance on understanding and documenting internal control, relying on internal control risk assessment, and relying on design and implementation of internal control) in electronic accounting systems.The study recommended that the external auditor should use his personal judgment and exercise professional scepticism in evaluating the internal control review in electronic accounting systems, and the need to increase interest in developing effective internal control systems for computerized accounting systems, which are characterized by providing the appropriate security for the systems so that the systems can provide information characterized by reliability from in order to make decisions, these systems must be integrated with other administrative and organizational systems in the organization.